The Influence of Principal’s Strategy and Work Climate on Teacher Professionalism at SMP Katolik Gonzaga Tomohon - Rahel Gabriela Lolong; Jefry Sony Junus Lengkong; Zoya Febrina Sumampouw (International Journal of Science and Environment (IJSE), 2026)
This study aims to analyze the influence of the principal's strategy and work climate, both partially and simultaneously, on teacher professionalism at SMP Katolik Gonzaga Tomohon. Using a quantitative associative approach with an ex-post facto design, this research involved the entire teacher population of 40 individuals as respondents through a total sampling technique. Data were collected using a Likert scale questionnaire that had been tested for validity and reliability and were analyzed using multiple linear regression. The results showed that: (1) The principal's strategy has a positive and significant effect on teacher professionalism (t=3.626; p<0.001) and is the most dominant variable; (2) The work climate has a positive and significant effect on teacher professionalism (t=2.637; p=0.012); and (3) Simultaneously, the principal's strategy and work climate have a significant effect on teacher professionalism, contributing 74.9% (=0.749). These findings confirm that improving teacher professionalism at SMP Katolik Gonzaga Tomohon heavily depends on the synergy between planned managerial policies and the creation of a conducive working atmosphere.